Comparative analysis of clinical characteristics and outcomes between carbapenem-resistant and carbapenem-sensitive Klebsiella pneumoniae infections: insights from a tertiary hospital in Northern China - Wang, Bu; Zhang, Wei; Zhang, Hongxia; Li, Maochen; Zhang, Zhihua; Peng, Xiaocui; Wang, Na; Song, Ning (Frontiers in Medicine, 2025)
BackgroundTo compare the risk factors, clinical outcomes, and mortality rates between carbapenem-resistant Klebsiella pneumoniae (CRKP) and carbapenem-sensitive Klebsiella pneumoniae (CSKP) infections.MethodsA retrospective cohort study was conducted on patients with Klebsiella pneumoniae infections admitted to a tertiary hospital in Zhangjiakou, China. The research period is from January 2021 to December 2022. Data were analyzed using SPSS 24.0 and R. Univariate analysis identified potential risk factors for CRKP infections using appropriate statistical methods, followed by multivariable logistic regression to determine independent risk factors. Mortality rates between CRKP and CSKP groups were compared using chi-square tests, and survival curves were generated with the Kaplan–Meier method.ResultsThe study included 283 patients, with 104 (36.7%) infected by CRKP and 179 (63.3%) by CSKP. CRKP patients had significantly higher body temperature, white blood cell counts, and inflammatory markers, while showing lower diastolic blood pressure and oxygen saturation (p < 0.05). CRKP infections were predominantly found in the ICU (49%) and mainly isolated from sputum (59%). Independent risk factors for CRKP included elevated C-reactive protein (OR = 1.02) and solid tumors (OR = 18.186). CRKP patients experienced longer hospital stays (25 days vs. 12 days for CSKP), longer ICU stays (13 days vs. 7 days), and higher 30-day mortality (23.1% vs. 17.9%, p = 0.012). The deceased group had elevated procalcitonin and creatinine levels, longer prothrombin time, and a greater need for mechanical ventilation compared to survivors (p < 0.05).ConclusionPatients with CRKP infections had higher mortality rates and longer hospital stays than those with CSKP infections. Previous hospitalization, hospitalization in an ICU, and mechanical ventilation were independent risk factors for CRKP infection.